Social media mining : an introduction - Zafarani, Reza, 1983-; Abbasi, Mohammad Ali, 1975-; Liu, Huan, 1958- (Cambridge : Cambridge University Press, 2014)
The growth of social media over the last decade has revolutionized the way individuals interact and industries conduct business. Individuals produce data at an unprecedented rate by interacting, sharing, and consuming content through social media. Understanding and processing this new type of data to glean actionable patterns presents challenges and opportunities for interdisciplinary research, novel algorithms and tool development. Social Media Mining integrates social media, social network analysis, and data mining to provide a coherent platform to understand the basics and potentials of social media mining. It introduces the unique problems arising from social media data and presents fundamental concepts, emerging issues, and effective algorithms for network analysis and data mining. Suitable for use in advanced undergraduate and beginning graduate courses as well as professional short courses, the text contains exercises of different degrees of difficulty that improve understanding and help apply concepts, principles and methods for social media mining.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Data mining; Social media -- Research; Behavioral assessment -- Data processing; Webometrics